PEMAKNAAN “TWITTER” PADA PENGGUNANYA BERDASARKAN KONSEP DIRI (Studi Fenomenologi Pengguna “Twitter” di Wilayah Jakarta) - Hadiono Afdjani; Rahma Fadjrianti (Communication, 2012)
The research objective was to determine the meaning of self-concept of open and closed user "Twitter" in the Jakarta area. This study in constructivist paradigm, with a qualitative approach. Phenomenology is the study methods exist. Data collection with primary and secondary data. Primary data with in-depth interviews and observation, while the secondary data from the literature is to get media, online and so on. The results showed that of the ten informants were interviewed, there are various self-concept varies according to their need to use "Twitter". Of the ten informants, there were four informants who had an open self-concept, self-concept has an the rest are closed. These differences greatly affect the user's "Twitter" in meaning "Twitter".